2003
DOI: 10.1677/jme.0.0300013
|View full text |Cite
|
Sign up to set email alerts
|

Putative functional characteristics of human estrogen receptor-beta isoforms

Abstract: Estrogen receptors (ERα and ERβ) are clearly multifaceted in terms of structure and function. Several relatively abundant ERβ isoforms have been identified, which can be differentially expressed in various tissues. In order to provide insight into the possible role of the ERβ family in breast tissue a study of the putative functions of the human (h) ERβ1, hERβ2 and hERβ5 isoforms was undertaken. Only hERβ1 was found to bind ligand, which induced conformational changes as determined by protease digestion assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 41 publications
4
107
0
4
Order By: Relevance
“…In contrast, ERb2/bcx lacks 61 amino acids normally found at the C-terminus of ERb1 and instead contains novel 27 amino acids that do not encode a functional AF-2 domain (Ogawa et al, 1998b). Studies in vitro have shown that ERb2/bcx-containing constructs do not bind oestradiol and that neither can they induce gene expression via oestrogen response elements (EREs) in reporter assays (Ogawa et al, 1998b;Peng et al, 2003;Sierens et al, 2004). Interest in determining whether ERb2/bcx is expressed in breast and other cancers has been fuelled by studies using transfected cells that have claimed that coexpression of ERb2/bcx with ERa results in reduced activation of ERE-containing reporter constructs (Ogawa et al, 1998b;Peng et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ERb2/bcx lacks 61 amino acids normally found at the C-terminus of ERb1 and instead contains novel 27 amino acids that do not encode a functional AF-2 domain (Ogawa et al, 1998b). Studies in vitro have shown that ERb2/bcx-containing constructs do not bind oestradiol and that neither can they induce gene expression via oestrogen response elements (EREs) in reporter assays (Ogawa et al, 1998b;Peng et al, 2003;Sierens et al, 2004). Interest in determining whether ERb2/bcx is expressed in breast and other cancers has been fuelled by studies using transfected cells that have claimed that coexpression of ERb2/bcx with ERa results in reduced activation of ERE-containing reporter constructs (Ogawa et al, 1998b;Peng et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The situation is complicated further by the identification of a number of splice variant isoforms of the human ERb gene (Moore et al, 1998), the mRNAs for which have been detected in breast cancer tissues and breast cancer cell lines (Fuqua et al, 1999;Speirs et al, 2000;Poola et al, 2002a, b). Studies in vitro have suggested that ERb isoforms with deletions of selected exons, or with alternative splicing at the C-terminus, may act as dominant-negative inhibitors of full-length ERa and/or ERb (Ogawa et al, 1998b;Inoue et al, 2000;Peng et al, 2003).…”
mentioning
confidence: 99%
“…Using IHC, it has been shown that differential expression of ERbwt and ERbcx may be used as a prognostic marker in human prostate (Fujimura et al 2001). Peng et al (2003) showed that all ERb isoforms inhibited ERa transcriptional activity on an ERE, while only ERbwt had transcriptional activity of its own. It has been shown, using cDNA microarrays in MCF-7 cells stably transfected with ERbwt and ERbcx MCF-7, that these two isoforms inhibit ERa function differently (Omoto et al 2003).…”
Section: Er Isoformsmentioning
confidence: 98%
“…ERb is expressed in both normal and neoplastic human breast tissue [3,4] but its role in either is only beginning to be understood. In animal studies, while ERa has been shown to be essential for normal mammary gland development, ERb effects are more subtle, with roles in terminal differentiation [5] and modulation of ERa activity being described [6][7][8]. In contrast to ERa, published data suggest that ERb expression declines during breast tumorigenesis [3,9].…”
Section: Introductionmentioning
confidence: 99%